ANALISIS NILAI PENDIDIKAN KARAKTER ANAK USIA DINI DALAM KITAB “WASHOYA AL-ABAA’LIL ABNA’KARANGAN KH.BISRI MUSTOFA - Ulin Ni’mah; Fitrotul Hikmah (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2022)
The introduction of the book Washoya Al-Aba 'Li Al-Abna' related to character education. The research used in this study is qualitative using a philological approach, data collection techniques using literature study, observation, documentation, analysis techniques. The results of this study show that the values of character education in the book Washoya Al-Aba' Li Al- Abna' which includes religion, tolerance, discipline, hard work, creative, independent, national spirit, love for the homeland, respect for achievement, love for peace, care for the environment, care for social and responsibility. The relevance of character education in the Washoya Al-Aba 'Li Al-Abna' for early childhood can be used as a reference in instilling the value of character education through the social environment of early childhood. The character education can be implemented with the habituation method. Research suggestions are to form collaboration between educators and parents in getting involved in increasing full attention to character development in early childhood.